Basmajian-type inequalities for maximal representations - Fanoni, Federica; Pozzetti, Maria Beatrice (Journal of differential geometry, 2020)
For suitable metrics on the locally symmetric space associated to a maximal representation, we prove inequalities between the length of the boundary and the lengths of orthogeodesics that generalize the classical Basmajian’s identity from Teichmüller theory. Any equality characterizes diagonal embeddings.
First available in project euclid: 3 December 2020
Gesehen am 07.01.2021